A new approach for the topical treatment of acne vulgaris by clindamycin HCL supported on kalion - Baghdad Science Journal (مجلة بغداد للعلوم, 2006)
Has been studied both processes Almetzaz and extortion of a substance Alklanda Maysan different amounts of Alcaúlan Guy 70% alcohol solution using the method when the wavelength